2003
DOI: 10.1007/s00464-002-9112-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, unicenter study comparing laparoscopic and open treatments of acute appendicitis

Abstract: On the basis of the conducted study, it may be assumed that laparoscopic appendectomy is a safe procedure, and that postoperative morbidity is comparable with that for a conventional operation. There was less postoperative pain and shorter recovery time after laparoscopic surgery than after the open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 16 publications
6
70
1
1
Order By: Relevance
“…It has an added advantage of minimal tissue trauma [19]. It is fast, easy to perform, and expected to decrease overall cost of LA.…”
Section: Discussionmentioning
confidence: 99%
“…It has an added advantage of minimal tissue trauma [19]. It is fast, easy to perform, and expected to decrease overall cost of LA.…”
Section: Discussionmentioning
confidence: 99%
“…In the prolonged follow-up, symptoms suggesting pericecal abscess, reported in the literature as a serious complication of laparoscopic appendectomy (13), were found in two cases (1.56%). Performed CT imaging of abdominal cavity demonstrated fluid collections …”
Section: Resultsmentioning
confidence: 83%
“…Many authors foresees Laparoscopic surgery as a reliable future tool for intraabdominal surgical pathologies in order to provide less invasiveness with maximum comfort and outcomes 6,7 . Several studies [8][9][10][11][12][13][14][15] have shown that laparoscopic appendectomy is safe with faster recovery and least wound complication.…”
Section: Discussionmentioning
confidence: 99%